Experimental Investigation of the Biomass Catalytic Pyrolysis Process to Produce the Combustible Gases with the High Calorific Value - Yury Kosivtsov; Esther Sulman; Yury Lugovoy; Anna Kosivtsova; Antonina Stepacheva (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The study is devoted to the low-temperature catalytic pyrolysis of biomass. The pyrolysis of peat was conducted using natural aluminosilicates and synthetic zeolites. It was found that the pore size of the mineral strongly affects the catalytic activity and provides the processing of the hydrocarbons forma-tion reactions. Bentonite clay was found to be the most effective catalyst for the biomass pyrolysis proc-ess. The use of bentonite clay as an addition to peat allows improving structural (strength, porosity) and sorption characteristics (sorption rate) of the molded compositions and can serve as a catalyst dur-ing its subsequent thermal conversion. The amount of gases obtained using natural aluminosilicate as a catalyst increased by 2 times compared to the non-catalytic process. The calorific value of the prod-ucts obtained was higher due to the light hydrocarbons formation. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).